Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5423/ppj.oa.12.2015.0259
|View full text |Cite|
|
Sign up to set email alerts
|

The Effects of High Temperature on Infection by Potato virus Y, Potato virus A, and Potato leafroll virus

Abstract: We examined the effects of temperature on acquisition of Potato virus Y-O (PVY-O), Potato virus A (PVA), and Potato leafroll virus (PLRV) by Myzus persicae by performing transmission tests with aphids that acquired each virus at different temperatures. Infection by PVY-O/PVA and PLRV increased with increasing plant temperature in Nicotiana benthamiana and Physalis floridana, respectively, after being transmitted by aphids that acquired them within a temperature range of 10–20°C. However, infection rates subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…Similarly, Chung et al [20] have shown that virus acquisition of Potato virus Y, Potato virus A and Potato leafroll virus , decreased when temperature was higher than 20°C. Concerning severe drought, it has long been known that viral infection can protect the host plants by delaying irreversible wilting [21].…”
Section: Introductionmentioning
confidence: 87%
“…Similarly, Chung et al [20] have shown that virus acquisition of Potato virus Y, Potato virus A and Potato leafroll virus , decreased when temperature was higher than 20°C. Concerning severe drought, it has long been known that viral infection can protect the host plants by delaying irreversible wilting [21].…”
Section: Introductionmentioning
confidence: 87%
“…It has been noted that the optimum temperature for plant virus transmission is pathosystem-dependent, and might differ slightly depending on the transmission step considered [47]. While the two potyviruses Potato virus A (PVA) and Potato virus Y (PVY) and PLRV are better transmitted, when acquisition by M. persicae is realised at 20 • C, the optimal temperature for further establishment of the infection differs according to virus species [48]. Optimal infection of PVA-or PVY-inoculated N. benthamiana occurs at 20 • C, while a temperature of 25 • C allows for the best disease development in PLRV-inoculated P. floridana [48].…”
Section: Impact Of Abiotic Stresses On Viral Transmissionmentioning
confidence: 99%
“…In recent years, there have been some reports on the effects of other abiotic factors, namely CO 2 , O 3 , and water stress, on the spread of viral diseases as a consequence of the extreme environmental changes [48,[51][52][53][54][55][56][57][58]. Dader and colleagues [53] thoroughly examined the impact of elevated CO 2 levels (eCO 2 ) on M. persicae life history, feeding behaviour, and the virus transmission ability of Cucumber mosaic virus (CMV; cucumovirus) to pepper plants (Capsicum annuum), transmitted in a non-circulative manner.…”
Section: Impact Of Abiotic Stresses On Viral Transmissionmentioning
confidence: 99%
“…Temperature affects many plant–pathogen interaction systems, including the interaction of potato and potato viruses. There are studies on temperature‐dependent differences in potato infection by various important potato viruses such as potato virus Y (PVY), potato virus X (PVX), potato virus A (PVA), and potato leafroll virus (PLRV; Adams et al ., 1986; Chung et al ., 2016; Szajko et al ., 2019). However, there is a lack of such research on the influence of temperature on potato infection by PVM.…”
Section: Introductionmentioning
confidence: 99%